Synthesis, photochemical and photophysical properties of phthalocyanine derivatives - Maqanda, Weziwe Theorine (Rhodes University, Faculty of Science, Department of Chemistry, 2005)
Substituted zinc and magnesium phthalocyanine and porphyrazine derivatives were synthesized according to the reported procedures. The magnesium and zinc phthalocyanine and porphyrazine derivatives were synthesized by ring enlargement of subphthalocyanine and statistical condensation of the two phthalonitrile derivatives. Characterization of the complexes involved the use of infrared spectroscopy, nuclear magnetic resonance spectroscopy, ultraviolet and visible spectroscopy, and Maldi-TOF spectroscopy (for selected compounds) and elemental analysis. Photochemical and photophysical properties of the complexes in non-aqueous solution was then investigated. Photobleaching quantum yields are in order of 10â »â µ indicating their relative photostability. Complexes containing more electron-donating substituents were more easily oxidized. For complexes 66 and 69 (as these complexes have the same number of substituents but differ in the metal center) photobleaching quantum yield for the ZincPc complex 69 was slightly less than that of the MgPc complex 66. Singlet oxygen quantum yields of the various complexes in DMSO using diphenylisobenzofuran (DPBF) as a quencher in organic solvents were determined. Singlet oxygen quantum yields of the complexes range from 0.23 to 0.67. High values of Î¦[subscript]Î” ZnPc complexes was observed compared to the corresponding MgPc, complexes. This was evidenced by complexes 66 and 69 with Î¦[subscript]Î” values of Î¦[subscript]Î” = 0.26 and 0.40, respectively. Varying number of phenoxy substituents, complex 71 gave significantly large value of Î¦[subscript]Î” compared to 70 (that is, the presence of more electron-donating substituted group, gave higher singlet oxygen quantum yields (0 .67 and 0.25 for 71 and 70 repectively). The triplet quantum yields and triplet lifetimes were determined by laser flash photolysis for selected compounds. The triplet quantum yields increase as the number of substituents increases e.g 68 > 67 > 66. Comparing porphyrazine complexes (63, 64 and 65), 63 with benzene attached to the ring, has higher triplet state lifetime (420 Î¼s) compared to 64 and 65 containing long alkyl chain and tertbutyl substituents, 350 and 360 Î¼s,respectively). The observed Î¦[subscript]f values for 68 and 63 were quiet suprising, since low values are observed compared to the rest of the complexes (e.g 0.03 and 0.02 respectively). Although these values seem so low, they are sufficient for fluorescence imaging applications. The Î¦[subscript]f values for the complexes under study are within the range reported for complexes currently used for PDT.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Photochemotherapy; Phthalocyanines; Zinc; Magnesium